2011
DOI: 10.1111/j.2044-8295.2010.02013.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manipulating context-specific information on perceptual-cognitive processes during a simulated anticipation task

Abstract: We manipulated contextual information in order to examine the perceptual-cognitive processes that support anticipation using a simulated cricket-batting task. Skilled (N= 10) and less skilled (N= 10) cricket batters responded to video simulations of opponents bowling a cricket ball under high and low contextual information conditions. Skilled batters were more accurate, demonstrated more effective search behaviours, and provided more detailed verbal reports of thinking. Moreover, when they viewed their opponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
118
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 25 publications
7
118
2
3
Order By: Relevance
“…It has been shown that expert sport performers are more adept at picking up low-level biological motion information from an opponent during anticipation (for reviews, see Müller & Abernethy, 2012;. However, it has been reported that experts are able to use higher-order cognition to harness contextual information from a scene in order to inform their anticipation judgements (McRobert, Ward, Eccles, & Williams, 2011). Rather than relying solely on kinematic cues, they formulate their decisions through the pickup of additional contextual information (e.g., situational probabilities; Abernethy et al, 2001).…”
Section: Anxiety Anticipation and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that expert sport performers are more adept at picking up low-level biological motion information from an opponent during anticipation (for reviews, see Müller & Abernethy, 2012;. However, it has been reported that experts are able to use higher-order cognition to harness contextual information from a scene in order to inform their anticipation judgements (McRobert, Ward, Eccles, & Williams, 2011). Rather than relying solely on kinematic cues, they formulate their decisions through the pickup of additional contextual information (e.g., situational probabilities; Abernethy et al, 2001).…”
Section: Anxiety Anticipation and Contextmentioning
confidence: 99%
“…Rather than relying solely on kinematic cues, they formulate their decisions through the pickup of additional contextual information (e.g., situational probabilities; Abernethy et al, 2001). McRobert et al (2011) reported that, when displaying video clips of a cricket bowler to skilled and less-skilled batters, both groups performed better when six bowls from the same bowler were displayed consecutively (high-context) in comparison to six deliveries from six different bowlers (low-context). This conceptualisation of the uses of contextual information is akin to the interactive encoding model proposed by Dittrich (1999).…”
Section: Anxiety Anticipation and Contextmentioning
confidence: 99%
“…The positive effect of providing contextual information to participants in addition to postural information has been demonstrated in several sports (for a review, see Cañal-Bruland & Mann, 2015). Researchers have demonstrated higher levels of anticipation performance CONTEXTUAL INFORMATION AND ANTICIPATION 6 when participants are provided with contextual information in the form of scores and number of balls and strikes in baseball (Paull & Glencross, 1997), increased exposure to the bowler in cricket (McRobert, Eccles, Ward, & Williams, 2011) and knowledge of the opponent's action preferences in soccer (Navia, van der Kamp, & Ruiz, 2013). In tennis, Crognier and Féry (2005) demonstrated that players anticipated more accurately in a high context, which they termed high tactical initiative, condition in which they were allowed to impose their game on the opponent over a series of shots, compared to when they were not allowed to do so and no shots were played prior to the opponent's occluded passing shot.…”
Section: Contextual Information and Anticipationmentioning
confidence: 99%
“…Increasingly, researchers have collected data for perceptual and cognitive process measures in the same study so as to establish much more fully the processes contributing to performance differences (Afonso & Mesquita, 2013;McRobert et al, 2011). While the visual search strategy employed is dependent on the task-constraints (Roca, Ford, McRobert, & Williams, 2013;Williams, Janelle, & Davids, 2004), skilled performers have usually been shown to employ different strategies to those of their less-skilled counterparts (for a review, see Mann et al, 2007).…”
Section: Contextual Information and Anticipationmentioning
confidence: 99%
See 1 more Smart Citation